2017
DOI: 10.1016/j.jff.2017.09.038
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intervention with green dwarf banana flour (Musa sp. AAA) modulates oxidative stress and colonic SCFAs production in the TNBS model of intestinal inflammation

Abstract: Dietary products with prebiotic properties have been used to promote protective effects during inflammatory process. Prebiotics are source of short chain fatty acids (SCFAs) that have been associated with anti-inflammatory effects. Banana (Musa sp. AAA) is rich in resistant starch, which is used by colonic microbiota to SCFAs production. For this, we used the trinitrobenzenesulphonic acid model of intestinal inflammation to evaluate whether intestinal anti-inflammatory effect is related to prebiotic effects. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 54 publications
1
18
1
1
Order By: Relevance
“…Propionate production was lower than that of acetate in our study, which is consistent with the results reported by Almeida‐Junior et al. (2017). Propionate produced by the gut microbiota is absorbed and metabolized by the liver (Wong et al., 2006).…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…Propionate production was lower than that of acetate in our study, which is consistent with the results reported by Almeida‐Junior et al. (2017). Propionate produced by the gut microbiota is absorbed and metabolized by the liver (Wong et al., 2006).…”
Section: Resultssupporting
confidence: 94%
“…Butyrate was detected at the lowest amounts, up to 0.6 mg/mL detected at 24 hr; however, this level was still significantly higher than that of the control (0.04 mg/mL) ( P < 0.05). Almeida‐Junior, Curimbaba, Chagas, Quaglio, and Di Stasi (2017) observed that acetate production was the highest among all the SCFAs when green dwarf banana flour was used to perform dietary intervention experiments, and during the fermentation of banana fructan (Shalini et al., 2017). Acetate can lower the pH in the colon, providing antibacterial effects (Teitelbaum & Walker, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Green banana-supplemented diets [ 29 ] and B. coagulans spores [ 15 ] have each previously been shown to reduce clinical diarrheal episodes, in line with the observations on DDS-induced mice in the current study. The anti-diarrheic effect of GBRS could be due to its high RS content that, upon reaching the caecum/colon, is metabolized by bacteria to SCFAs [ 27 ]. These, in turn, stimulate salt and water absorption, provide energy and induce a trophic effect on the colon [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dried green banana (GB), ground to a flour, is a high volume natural food source of RS. It has been demonstrated to prevent intestinal inflammation [ 26 ] and modulate oxidative stress [ 27 ] in animal models of colitis. It can also impart anti-diarrhoeal effects in children [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hal ini menunjukan bahwa jenis dan strain probiotik yang diujikan mempengaruhi nilai aktivitas prebiotik (Agustina, 2016). Fermentasi RS oleh BAL probiotik di dalam usus besar menghasilkan asam lemak rantai pendek dan menyebabkan terjadi penurunan pH dalam usus sehingga mampu menekan pertumbuhan mikroorganisme patogen secara selektif serta menstimulasi pertumbuhan BAL probiotik (Almeida-Junior et al, 2017). Penelitian secara in vivo membuktikan babi yang diberi pakan RS dapat mening-katkan kandungan asam lemak rantai pendek pada sekum dan kolon (Haenen et al, 2013;Fang et al, 2014).…”
Section: Kemampuan Pertumbuhan Probiotikunclassified